Implications of macroeconomic volatility in the Euro area - Niko Hauzenberger; Maximilian Böck; Michael Pfarrhofer; Anna Stelzer; Gregor Zens (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2018)
In this paper we estimate a Bayesian vector autoregressive model with factor stochastic volatility in the error term to assess the effects of an uncertainty shock in the Euro area. This allows us to treat macroeconomic uncertainty as a latent quantity during estimation. Only a limited number of contributions to the literature estimate uncertainty and its macroeconomic consequences jointly, and most are based on single country models. We analyze the special case of a shock restricted to the Euro area, where member states are highly related by construction. We find significant results of a decrease in real activity for all countries over a period of roughly a year following an uncertainty shock. Moreover, equity prices, short-term interest rates and exports tend to decline, while unemployment levels increase. Dynamic responses across countries differ slightly in magnitude and duration, with Ireland, Slovakia and Greece exhibiting different reactions for some macroeconomic fundamentals.
Keywords: C30; F41; E32; 330; Bayesian vector autoregressive models; factor stochastic volatility; uncertainty shocks